Where biodiversity, traditional knowledge, health and livelihoods meet: Institutional pillars for the productive inclusion of local communities (Brazil case study) - Radhika Lal; Waldemiro Francisco Sorte Junior (International Policy Centre for Inclusive Growth (IPC-IG), 2011)
[Introduction ...] The paper is organised as follows: Section 2 provides a brief background of the economic and social context of rural development issues in Brazil. Section 3 explores Brazil's productive inclusion approach and draws implications for the design of natural-resource-based production chains and the delivery of services (e.g. phytotherapies and phytocosmetics). Section 4 of the paper provides a survey of issues at the intersection of biodiversity, traditional medicine, drug discovery and health care. It discusses Brazil's National Programme on Medicinal Plants and Herbal Medicines (Programa Nacional de Plantas Medicinais e Fitoterápicos, PNPMF), and alludes to the experiences of countries such as India and China so as to place the discussion about Brazil's approach within a broader cross-country context. In light of Brazil's multi-stakeholder approach to productive inclusion, the paper explores the roles of community-based networks and applied public research institutions which can serve to stimulate social and technological innovation and help to address structural asymmetries in the relation between the private sector and local communities. Section 5 focuses on access and benefit-sharing issues. Section 6 concludes the paper by drawing institutional lessons and highlighting issues for policy discussion.
Keywords: 330